2003
DOI: 10.1021/jf020765l
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Components and Aroma Active Compounds in Aqueous Essence and Fresh Pink Guava Fruit Puree (Psidium guajava L.) by GC-MS and Multidimensional GC/GC-O

Abstract: Characterization of the aromatic profile in commercial guava essence and fresh fruit puree by GC-MS yielded a total of 51 components quantified. Commercial essence was characterized to present a volatile profile rich in components with low molecular weight, especially alcohols, esters, and aldehydes, whereas in the fresh fruit puree terpenic hydrocarbons and 3-hydroxy-2-butanone were the most abundant components. In the olfactometric analyses totals of 43 and 48 aroma active components were detected by the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 14 publications
1
60
1
4
Order By: Relevance
“…The presence of a-copaene in aqueous essence of P. guajava has been reported previously (Jordan et al 2003).…”
Section: Identification Of Anticancer Compounds By Gc-msmentioning
confidence: 56%
“…The presence of a-copaene in aqueous essence of P. guajava has been reported previously (Jordan et al 2003).…”
Section: Identification Of Anticancer Compounds By Gc-msmentioning
confidence: 56%
“…Pentadecanal, slicky odor of waxy and floral 31) , was found in black rice bran while 6, 10, 14-trimethyl-2-pentadecanone was found in red rice bran. (E)-b-ocimene, presenting in red rice bran, was responsible for wet, cloth and fruity odor 32) . Caproic 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 1097 1100 1101 1101 1114 1132 1145 1152 1161 1162 1169 1172 1175 1180 1181 1189 1192 1199 1200 1202 1212...…”
Section: Resultsmentioning
confidence: 99%
“…They worked on volatiles in Costa Rican guava fruit by a simultaneous steam distillation-solvent extraction method and found one hundred and seventy five compounds identified in the aroma concentrate by GC-sniffing technique. Jordan et al (2003), in a study characterizing guava fresh fruit puree aromatic profile by GC-MS, reported the quantification of 51 compounds. The volatile profile of guava fresh fruit puree has been characterized by the presence of terpenic hydrocarbons and 3-hydroxi-2-butanone as quantitatively the major components.…”
Section: Guava Nectar Processingmentioning
confidence: 99%
“…This technique is relatively low cost and easy of automation. An efficient extraction of chemical compounds is dependent on time, stirring, heat, pH and salt, and NaCl concentration (KATAOKA; LORD; PAwLISZYN, 2000). The SPME technique is based on chemical compound adsorption on a silica fiber covered by a stationary phase.…”
Section: Guava Nectar Processingmentioning
confidence: 99%